Stratifikasi Sosial Dalam Pendidikan di Probolinggo Pada Era Kolonial Belanda - Tiyo Eka Mayshurah; Abdus Sair (Journal of Urban Sociology, 2023)
This study aims to explore social stratification in education during the Dutch colonial era in Probolinggo. Previous studies have shown that various educational policies implemented by the Dutch in Probolinggo were intended to prepare administrative and manual labor workers who would play an important role in building the economy. However, these policies have actually resulted in unfair social stratification in society. Although native education offered opportunities to obtain an education, these schools were established with a specific purpose: to meet the needs of manual labor workers for the benefit of Dutch capital. Native education mostly provided basic skills needed to work in specific sectors. This study was conducted using a historical approach consisting of heuristic, criticism, interpretation, and historiography stages. The results confirm that Dutch colonial education policies in Probolinggo not only produced manual labor workers but also strengthened the position of the Dutch East Indies government.Keywords: Social Stratification, Education, Probolinggo, Dutch Colonial.